Teachers' Voices: Networked Technologies for EFL Classroom in The Border Area of Indonesia - Ramli, Ramli; Kusmaryani, Woro; Rosmayanti, Vivit; MB, Kamaluddin; Hermawan, Nanang (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research aimed at providing to insight on how ICT contributes to English language teaching. The target of research was 9 EFL secondary teachers in Tarakan Kalimantan Utara as the border area in Indonesia. Interview was also administered in the current study to elicit in-depth information on whether the teachers bring technological tools in the class, the types of technological tools to support their English class, and the reasons for effective use and non-use. The questionnaire consisted of 20 items that are divided into five main parts: teacher’s background, classroom settings, various use of technology, perceptions of technology, and factors affecting teacher use of technological tools. The data was derived from Likert scale questions in the questionnaire. The results of this research were that mostly students and teacher optimized smartphone and computer in the class and teachers involved various technological applications to support learning. All teachers agreed that technology is necessary for the classroom and integrating digital technology can help support the learning of students. Besides, the use of technology was mostly affected by external factors, facilities, workload, and support from head of department and as for internal factors, teachers’ skills, teachers’ interests, and confidence were the top-reported aspects.